Safety of thrombolysis in stroke mimics - Zinkstok, Sanne M.; Ringleb, Peter A. (Stroke, 2013)
Background and Purpose— - - Intravenous thrombolysis for acute ischemic stroke is beneficial within 4.5 hours of symptom onset, but the effect rapidly decreases over time, necessitating quick diagnostic in-hospital work-up. Initial time strain occasionally results in treatment of patients with an alternate diagnosis (stroke mimics). We investigated whether intravenous thrombolysis is safe in these patients. - - Methods— - - In this multicenter observational cohort study containing 5581 consecutive patients treated with intravenous thrombolysis, we determined the frequency and the clinical characteristics of stroke mimics. For safety, we compared the symptomatic intracranial hemorrhage (European Cooperative Acute Stroke Study II [ECASS-II] definition) rate of stroke mimics with ischemic strokes. - - Results— - - One hundred stroke mimics were identified, resulting in a frequency of 1.8% (95% confidence interval, 1.5-2.2). Patients with a stroke mimic were younger, more often female, and had fewer risk factors except smoking and previous stroke or transient ischemic attack. The symptomatic intracranial hemorrhage rate in stroke mimics was 1.0% (95% confidence interval, 0.0-5.0) compared with 7.9% (95% confidence interval, 7.2-8.7) in ischemic strokes. - - Conclusions— - - In experienced stroke centers, among patients treated with intravenous thrombolysis, only a few had a final diagnosis other than stroke. The complication rate in these stroke mimics was low.
Gesehen am 02.08.2021